Growth and yield of maize (Zea mays L.) as influenced by date of sowing and hybrids - Sridhara, Shankarappa; Sab, Dadapeer Belaghatta Hassan; Gopakkali, Pradeep (Journal of Agriculture and Applied Biology, 2020)
A field experiment was conducted at college of Agriculture, UAHS, Shivamogga during kharif 2015 to study the effect of date of sowing and hybrids on growth and yield of Maize (Zea mays L.). The experi-ment was laid out in randomized complete block design (RCBD) with factorial concept and replicated thrice. There were eight treatment combinations which includes four dates of sowing (15th June, 30th June, 15th July and 30th July) and two hybrids (PAC-740 and CP-818). Crop sown on 15th June recorded significantly higher plant height (201.03 cm), number of green leaves (3.03), leaf area (992.49 cm2), LAI (0.74), total dry matter (305.65 g), cob length (22.16 cm), kernels cob-1 (670.93), kernel yield cob-1 (230.95 g), test weight (43.08 g), kernel yield (7632.57 kg ha-1), stover yield (9512.56 kg ha-1) and har-vest index (44.52 %) as compared to other sowing dates. Among the hybrids CP -818 recorded significantly higher plant height (191.85 cm), number of green leaves (2.72), leaf area (954.32 cm2), LAI (0.71), total dry matter (277.65 g), cob length (19.81 cm), kernels cob-1 (541.88), kernel yield cob-1 (207.71 g), test weight (39.16 g), kernel yield (7060.72 kg ha-1), Stover yield (8839.98 kg ha-1) and harvest in-dex (44.44%) as compared to PAC-740. The interaction between dates of sowing and hybrids are non-significant.